(untitled) (Costa Rican Journal of Guidance & Counseling, 2023)
The choice of career and university at the end of secondary education represents a challenge for the student population, so facilitating spaces to accompany people from Vocational Guidance at this stage is of paramount importance to meet the needs that may arise, mainly because of the extent that this decision has in people’s lives. Therefore, precisely this article aims to reflect on the vocational needs presented by users of the Vocational-Occupational Guidance Center (COVO) of the University of Costa Rica, an Orientation service that aims to advise students in their career choice. Based on the mixed research approach, the biodata of the users of the center were analyzed quantitatively using the initial data sheet of the computerized system of the COVO, and qualitatively the experience of five people who used the service for the first time was used, distributed according to the type of user of this service. As the main result, it is determined that the most outstanding vocational needs in all kinds of users were those related to exploration and professional support; however, despite the similarity in vocational needs, it is evident that they do vary according to the type of user and that the life history influences each person.